1998
DOI: 10.1037/0894-4105.12.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical correlates of cognitive aging: Evidence from structural magnetic resonance imaging.

Abstract: To examine putative brain substrates of cognitive functions differentially affected by age the authors measured the volume of cortical regions and performance on tests of executive functions, working memory, explicit memory, and priming in healthy adults (18-77 years old). The results indicate that shrinkage of the prefrontal cortex mediates age-related increases in perseveration. The volume of visual processing areas predicted performance on nonverbal working memory tasks. Contrary to the hypotheses, in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
370
4
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 476 publications
(412 citation statements)
references
References 136 publications
36
370
4
2
Order By: Relevance
“…The egocentricity of older adults reflects the default position of a general self-prioritizing processing bias. In line with the decline in cognitive flexibility in this age group, however (e.g., Dempster, 1992;Raz, Gunning-Dixon, Head, Dupuis, & Acker, 1998;van der Linden, Brédart, & Beerten, 1994), they were less able than the younger group to suppress self-bias when it interfered with task performance.…”
Section: Flexibility Of Self-biasesmentioning
confidence: 78%
“…The egocentricity of older adults reflects the default position of a general self-prioritizing processing bias. In line with the decline in cognitive flexibility in this age group, however (e.g., Dempster, 1992;Raz, Gunning-Dixon, Head, Dupuis, & Acker, 1998;van der Linden, Brédart, & Beerten, 1994), they were less able than the younger group to suppress self-bias when it interfered with task performance.…”
Section: Flexibility Of Self-biasesmentioning
confidence: 78%
“…Rates are highest among the young (17% for ages 18-29), considerably less in middle age (4% for ages 30-59), and virtually non-existent in those over 60 (Miller 1991). While such figures may represent the "wisdom" commonly associated with aging, they may also reflect age-related brain changes (Bartzokis et al 2000;Coffey et al 1992;Gottfries et al 1983;Jernigan et al 1990;Lepage et al 1985;Lim et al 1992;Matsumae et al 1996;Pfefferbaum et al 1994;Raz et al 1998;Sullivan et al 1995;Wahlund et al 1990;Wang et al 1996), which alter the balance between the addicting versus the aversive effects of cocaine by diminishing the euphoric experience of drug intoxication. Consequently, the tendency to develop a dependence syndrome decreases and the capacity to discontinue use increases (Miller 1991;Cook and Harrell 1987;Facy et al 1991;Bartzokis et al 1999b,c).…”
Section: Discussionmentioning
confidence: 99%
“…In two other studies with subjects aged 18 to 80 years no relation could be established between brain volumes and neuropsychological test results after controlling for the effects of age [22,32]. However, in studies where only 55ϩ subjects were included a significant relation was found between limbic structures and memory test performance [13,14,32].…”
Section: Relation Between Brain Volumes and Cognitive Performancementioning
confidence: 92%
“…Only two studies have investigated the relation between regional brain atrophy and cognitive deterioration using quantitative (i.e. volumetric) analysis methods in a large sample [14,32]. A relation was found between limbic structures and memory in subjects over 55 years of age.…”
Section: Introductionmentioning
confidence: 99%